Gen-Z's Decision-Making: Impact of Attitudes, Knowledge, and Social Media on Halal Tourism Choices - Ilham, Arifin Muhammad; Ismail, Nurizal; Al-Ayubi, Solahuddin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
Halal tourism in Indonesia continues to show significant growth; however, there is still a lack of research that deeply explores how various factors influence Generation Z's (Gen-Z) decisions when choosing halal tourism destinations, particularly in Riau Province. With its rich cultural heritage and history closely tied to Islamic teachings, Riau Province presents an intriguing potential for further study. The aim of this research is to analyze the influence of attitudes, knowledge, and social media on the decision-making of Gen-Z in the Riau Province when selecting tourism destinations that adhere to halal principles. This study employs a quantitative analysis method using the Structural Equation Model – Partial Least Square (SEM-PLS) technique. The analysis results conclude that each mentioned variable has a direct and significant impact on the Decision to Choose Halal Tourism Destinations in the Riau Province. The Attitude variable has a direct and significant impact on the Decision to Choose Halal Tourism Destinations. This explains that individuals' attitudes towards specific aspects related to halal tourism can influence the decision-making of Gen-Z in choosing those destinations. The Knowledge variable also has a direct and significant impact on the Decision to Choose Halal Tourism Destinations. This indicates that tourists' knowledge level about halal tourism destinations positively contributes to their decision-making in selecting those destinations. The Social Media variable also has a direct and significant impact on the Decision to Choose Halal Tourism Destinations. This illustrates that information or influence from social media plays a crucial role in tourists' decisions to choose halal tourism destinations. The government and tourism managers need to focus on awareness and education, strengthen social media management as an effective marketing tool, and enhance digital infrastructure. The concept of halal tourism and corresponding services, along with collaboration with local communities and religious leaders, are also key factors.